ANALISIS PENGARUH KUALITAS PRODUK DAN PROMOSITERHADAP KEPUTUSAN PEMBELIAN LIQUIDBERCUKAI DI DJAWAY VAPE STOREDI PANDEGLANG - Miftah Faiz Ali Ramdhani; Tubagus Rizki Chandra Nugraha (NIAGARA Scientific Journal, 2023)
Product quality and promotion are important things that can influence purchasing decisions, the better the quality of the products you have and supported by attractive promotions, it will be able to provide encouragement to consumers in making purchasing decisions on marketed products. This study aims to determine whether there is an effect of product quality on purchasing decisions, and whether there is an influence of promotion on purchasing decisions and whether there is an influence of product quality and promotion on purchasing decisions of excise liquid products. The population in this study were all consumers of the Djaway Vapestorestore. Sampling in this study used the slovin formula with the results of 100 respondents being the sample. The data analysis technique used validation test, reliability test, descriptive analysis, multiple linear regression, classical assumption test, t test, f test, and coefficient of determination. The results of this study indicate that the product quality variable has a significant effect on purchasing decisions, and the promotion variable has a significant effect on purchasing decisions. Based on the simultaneous test of product quality and promotion variables have a significant effect on purchasing decisions.